Italian painting before 1400 (London Roland Collection, 1993)
Examines the methods and techniques of Tuscan panel paintings of the Trecento, using the detailed instruction in Cennino Cennini's Libro del'Arte (circa 1397), experts from the National Gallery Conservation and Framing Departments demonstrate the many stages of creating an altarpiece, including making gesso, water gliding, burnishing, pigment grinding, and painting with egg tempura.
VHS format.
Written and narrated by James Heard.
Title on cassette label :Art in the making, Italian painting before 1400.
Keywords: Panel painting, Italian; Panel painting, Medieval -- Italy